Apricot Kernel Oil Ameliorates Cyclophosphamide‐Associated Immunosuppression in Rats. Issue 8 (4th June 2016) - Tian, Honglei; Yan, Haiyan; Tan, Siwei; Zhan, Ping; Mao, Xiaoying; Wang, Peng; Wang, Zhouping
Abstract: The effects of dietary apricot kernel oil (AKO), which contains high levels of oleic and linoleic acids and lower levels of α‐tocopherol, were evaluated in a rat model of cyclophosphamide‐induced immunosuppression. Rats had intraperitoneal injection with cyclophosphamide to induce immunosuppression and were then infused with AKO or normal saline (NS) for 4 weeks. Enzyme‐linked immunosorbent assays were used to detect antimicrobial factors in lymphocytes and anti‐inflammatory factors in hepatocytes. Hematoxylin & eosin staining was conducted prior to histopathological analysis of the spleen, liver, and thymus. Significant differences were observed between the immune functions of the healthy control group, the normal saline group, and the AKO group. Compared to the normal saline‐treated group, lymphocytes isolated from rats administered AKO showed significant improvement in immunoglobulin (Ig)A, IgM, IgG, interleukin (IL)‐2, IL‐12, and tumor necrosis factor‐α (TNF‐α) levels ( p < 0.01). Liver tissue levels of malondialdehyde and activities of superoxide dismutase and glutathione peroxidase indicated reduced oxidative stress in rats treated with AKO ( p < 0.01). Dietary AKO positively affected rat growth and inhibited cyclophosphamide‐associated organ degeneration. These results suggested that AKO may enhance the immune system in vivo. These effects may reflect the activities of intermediate oleic and linoleic acid metabolites, which play a vital role in the immune system, and the α‐tocopherol in AKO may further enhance this phenomenon. Thus, the use of AKO as a nutritional supplement can be proposed to ameliorate chemotherapy‐associated immunosuppression.